Solomon Islands : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for the Solomon Islands reviews budget trends in the past decade and assesses medium-term budget prospects. Aid flows and revenue from import tariffs and logging are projected to decline. Spending pressures are likely to pick up considerably, owing to the need to increase spending on infrastructure and operations and maintenance. Demands for higher wages and greater public employment opportunities are likely to persist. As aid flows are scaled back, the government will need to provide at least some of the services currently provided by donor programs.